(untitled) (International Educators Conference, 2025)
Reading is one of the fundamental language skills necessary for effective communication and academic success in a foreign language. Developing strong reading skills enables learners to comprehend, analyze, and critically evaluate texts, which in turn supports their overall language proficiency. This article explores various strategies and approaches to improve learners’ reading skills in foreign languages, including extensive and intensive reading, use of authentic materials, vocabulary development, and interactive reading activities. The study also highlights the role of motivation, cultural context, and technological tools in enhancing reading comprehension. Ultimately, this paper provides practical recommendations for language teachers to design effective reading instruction that caters to diverse learner needs.